An exploration of risks and resources related to parental burnout among parents of adults with intellectual and developmental disabilities and behaviours that challenge in Atlantis, Western Cape, South Africa - Lategan, Maxeen (Department of Psychiatry and Mental Health, 2025)
Introduction: Parental burnout, an emerging phenomenon, may be experienced when there is a persistent imbalance between demands and resources in a parents' role. Parental burnout includes an overwhelming exhaustion related to parental duties, emotional distance from your child and the feeling of loss of accomplishment of your parenting role (Mikolajczak & Roskam, 2018). Against the backdrop of South Africa's history and remaining socio-economic challenges, it is likely for parents of persons with IDD and CB to develop parental burnout, considering the high parental stress that they endure. I conducted a scoping review using the Joanna Briggs Institute PRISMA-Scoping review guidelines to provide an overview of existing literature on risks and resources that may influence the development of parental burnout in parents of children, adolescents and adults with IDD and behaviours that challenge. The scoping review yielded five peer reviewed papers from high income countries. Papers mainly focused on (1) informal and formal support structures as protectors against parental burnout; (2) co-parenting and in addition to the balance between risks and resource elements, other elements that arose as influential on parental burnout, were (1) the characteristics of the child; (2) parental hypervigilance; (3) COVID19 stressors; and (4) religion as a coping mechanism. Overall, the findings of the scoping review suggested that parental burnout in this cohort is under researched both internationally and in South Africa, informing the purpose for my study. Study Aim: The study aimed to explore the stressors and resources among parents of adults who have intellectual and developmental disabilities (IDD) and co-occurring behaviours that challenge in Atlantis in the Western Cape, a province of South Africa. Methods: With permission from the research site and approval from the university's human research ethics committee, applying an exploratory phenomenological approach, I conducted nine semi-structured interviews to saturation. Research participants were not all parents but confirmed primary caregivers of adults with IDD and CB. The participants, all residents from Atlantis, were homogenous in their race as they were all people of colour. They were diverse in gender as both males and females were included and ages ranged between 38 and 72. Findings: I used Bronfenbrenner's (1979) ecological systems theory' and the ‘balance between risks and resources theoretical framework' (Mikolajczak & Roskam, 2018) to analyse the gathered data, applying thematic analysis principles. On micro level, the following themes were identified: (1) coming to grips with a diagnosis; (2) managing behaviours that are challenging; (3) parental personality; (4) emotional intelligence; (5) parental self-compassion and perfectionism; (6) gender; and (7) high parental chores and duties as opposed to time for leisure were identified. These are factors mediating parental burnout on an individual level. On meso level, the following themes were identified: (1) co- parenting; (2) the impact of siblings; and (3) the relationship between day care facilities and families. The relationships between these systems and how they influence parental burnout are considered. On macro level, (1) religious views; and (2) societal inclusivity was identified contributing factors. On exo level, (1) access to social grants; (2) access to education; (3) access to health care services and (4) access to therapeutic services were identified. Lastly, the chrono level considered how changes over time may mediate or expedite the development of parental burnout. Conclusion: The scoping review and semi structured interviews had overlapping themes whilst also sharing unique experiences including: (1) the difficulty in managing wonderous behaviour in an unsafe community, which is a challenge distinctive to the setting of this study; and (2) planning for the future. Research participants in my study were highly focused on having plans in place for their relative for continuity of care when they are no longer able to care for them. Although a few participants reported experiencing some of the signs of parental burnout, the findings suggest that they rely strongly on the protective factors to preserve and act with resiliency in the face of adversity.